Nasal Washing Training As An Effort To Increase The Resistance Of The Nasal Mucosa During The Covid-19 Pandemic At Putri Aisyiah Dinoyo Orphanage Malang City - Nimim Putri Zahara; Anung Putri Illahika; Risma Karlina Prabawati; Patmawati (DokTIn MEDIKA Jurnal Pengabdian Masyarakat, 2025)
Background: The Covid-19 pandemic spreads very rapidly through droplets that can enter the nose and mouth easyly, so training program to increase the resistance of the nasal mucosa are very important by washing the nose with istinsyaq-istintsar or with saline solution. Objective: This training program is expected to increase knowledge and skills regarding the importance of maintaining nasal hygiene at the Putri Aisyiah Dinoyo Orphanage, Malang City. Methods: This activity consists of three stages, counseling, discussion and training, then evaluation and data analysis. Results: The results of the evaluation of these activities are 100% of respondents know about the way the Corona virus enter the body and they know how to prevent it. As many as 95% of the respondents have actively performed nasal washing by istinsyaq- istintsar or with saline solution.